GAMBARAN PENGETAHUAN WUS TENTANG KB IMPLANT - Debi Novita Siregar (Universitas Prima Indonesia, 2018)
Keluarga Berencana (KB) is a way to adjust the interval between pregnancies and determine the number of children in the family. There are several methods of contraception that can be used for women such as birth control pills, KB injections, implants or implants, contraceptive devices (IUDs) and women's surgical methods (MOW), whereas men usually have periodic abstinence, condoms, intercourse, and male surgery method. The current National Keluarga Berencana (KB) Program is not only moving on the issue of family planning but also participating in other population programs that support the success of the Keluarga Berencana (KB) Program which will further result in improving family welfare. The purpose of this study is to know the description of knowledge of EFA women in the Ela Azmi Clinic in 2018. This type of research uses descriptive research method with a population jumped by 50 people. Sampling technique by way of saturated sampling. Result of research got majority of WUS have knowledge less about KB implant as much 22 people (44%). While the knowledgeable enough WUS as many as 18 people (36%), and good knowledge as many as 10 people (20.0%). It is recommended that WUS In order to always increase the knowledge of Implant Contraception so that aware of the use of Implant Contraception and to understand about function, benefit and effectiveness of contraception Implant so that KB / society become more familiar with and use of Implant Contraception is increasing.